2016
DOI: 10.1002/2016jd025711
|View full text |Cite
|
Sign up to set email alerts
|

Spatial‐temporal variation of near‐surface temperature lapse rates over the Tianshan Mountains, central Asia

Abstract: Adequate estimates of near‐surface temperature lapse rate (γlocal) are needed to represent air temperature in remote mountain regions with sparse instrumental records such as the mountains of central Asia. To identify the spatial and temporal variations of γlocal in the Tianshan Mountains, long‐term (1961–2011) daily maximum, mean, and minimum temperature (Tmax, Tmean, and Tmin) data from 17 weather stations and 1 year of temperature logger data were analyzed considering three subregions: northern slopes, Kaid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 58 publications
2
33
2
Order By: Relevance
“…The meteorological conditions clearly play an important role in defining the characteristics of the LRs on both sides of the northern sector of the SPI. Shen et al (2016) indicated that the role of water vapor in the air is an essential driver of the spatial pattern of LRs. Gentle LRs are associated with moister atmospheric conditions, as rising air parcels cool more slowly in a humid environment than in a dry environment.…”
Section: Lrs and Air Temperature Spatial Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…The meteorological conditions clearly play an important role in defining the characteristics of the LRs on both sides of the northern sector of the SPI. Shen et al (2016) indicated that the role of water vapor in the air is an essential driver of the spatial pattern of LRs. Gentle LRs are associated with moister atmospheric conditions, as rising air parcels cool more slowly in a humid environment than in a dry environment.…”
Section: Lrs and Air Temperature Spatial Patternsmentioning
confidence: 99%
“…However, due to the complex boundary layer meteorology of mountainous areas and the general lack of detailed on-glacier measurements (Hanna et al, 2017), constant and linear LRs are commonly used for glacier ablation estimations, rather than distributed air temperature fields for glacier ablation estimations (Ayala et al, 2015). This is a major simplification, as it has been widely recognized that air temperature LRs are spatially and temporally variable in mountainous regions (Petersen & Pellicciotti, 2011), both on-glacier (Ayala et al, 2015;Hanna et al, 2017;Shaw et al, 2017) and off-glacier (Heynen et al, 2016;Shen et al, 2016). Many studies use off-glacier data that do not account for the variability of the air temperature associated with katabatic boundary layer flows and the damping and ice surface cooling effect observed over glacier surfaces (Ayala et al, 2015;Carturan et al, 2015;Petersen & Pellicciotti, 2011;Petersen et al, 2013;Shaw et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the temperature lapse rate is crucial for representing mountain temperature and simulating snowmelt runoff in high‐elevation basins (Deng et al, ; Immerzeel et al, ; Li & Williams, ; Lundquist & Cayan, ). According to our field research, temperature lapse rates vary spatially and seasonally in the Tianshan Mountains (Shen et al, ), which has not been addressed in previous hydrological modeling studies (Dou et al, ; Xu et al, ; Zhang et al, ). Moreover, vegetation structure, soil type, geology, and morphological features were not considered in sufficient detail in previous studies (Liu et al, ; Sun et al, ; Xu et al, ).…”
Section: Introductionmentioning
confidence: 81%
“…Similar bias correction methods have frequently been used in the literature (Gao et al, ; Liu et al, ; Shea et al, ). The largest bias in winter temperature during the correction processes might be interpreted as a temperature inversion (Shen et al, ) which can be captured by local monitoring stations but not the ERA‐Interim temperature data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation